Demand Characteristics of Electricity in Residential Sector of Kathmandu Valley - Rajbhandhari, Utsav Shree; Poudel, Laxman; Bhattarai, Nawraj (Journal of the Institute of Engineering, 2020)
Planning for electricity demand is a vital as the characteristics of different electricity generation systems vary temporally – both hourly in a day as well as seasonally in a year. Thus, this study focuses on evaluating the demand characteristic of electricity in residential sector within urban boundaries of three districts in Kathmandu Valley. It has addressed variations in demand in form of load curve based on hourly peak demand during a day. The demand characteristics have been affected in recent years are primarily influenced by two factors – the trade debacle in 2015 and the end of load-shedding. A typical family with owned household would have highest demand with loads spread over various time of the day. While the one in rented family would have least demand level with most characteristic peaks. But in overall, there are peculiar morning and evening peaks, in addition to small early morning peak. The current technology interventions and electricity consumption pattern with reference in earlier years depicts the change in energy technology preference. The reduction in daily demand pattern as well as total electricity demand are majorly due to replacement of older technologies with more efficient appliances as well as reduced use of inverters for battery charging. Thus, it can be said that a stringent condition can enforce people to change to efficient technologies as well as proper supply can reduce unnecessary demand in battery charging. On other hand, similar trend, and hence the increase in electricity demand, can be anticipated in other flourishing urban areas of the country. Additionally, it is beneficial to have the demand characteristics of each sector separately - which can be useful to design the decentralized systems for specific sector.